Desfragmentando vacíos (2019)
"The project "Defragmenting gaps" is implemented in the buildings on the southern edge of the Plaza Antonio Nariño or commonly called Plaza de la Mariposa. This square is located next to Jimenez Avenue and between Carrera Décima and Caracas Avenue. The reason why the project was located in this place, was the interest found in the canalization of the San Francisco River occurred in the mid-twentieth century. This fact changed the square, since the river became a void in the city that nobody notices today. This emptiness is also transferred to the buildings on the edge of the square, specifically on the upper floors and what it produces is a series of urban ruins that deteriorate the quality of habitability of both the city and the people. Under this observed situation, the intention is to infiltrate the existing void by means of new programs (temporary housing, industry, education, spaces of leisure and recreation) that complement the area, so that in this way the social and spatial dynamics that are presented there can be strengthened."--Tomado del Formato de Documento de Grado.